Estimated budgets for separate-site swine production - Dhuyvetter, Kevin C.; Tokach, Michael D.; Jones, R.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Budgets were developed to help Kansas swine producers analyze the economics of separate-site production. Return on investment (ROI) was estimated at 9.5%in each of the three production phases. Returns over total costs were very sensitive to transfer price between phases (weaned pig and feeder pig price) as well as production efficiencies and input costs.
Keywords: Swine; Economics; Budgets; Separate-site production